COMMUNICATION MODELS AND COMMON BASIS FOR MULTICULTURAL COMMUNICATION IN LATVIA - Petersons, Andris; Khalimzoda, Ilkhom (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Different models serve not only as a frame for communication, they can help to rise problems as well as discuss them. This article introduces with the four communication models starting from Aristotle’s triangle model and ending with a more contemporary one. The authors try to find out, which is the most appropriate model for intercultural communication in Latvia? The empirical data collected from two focus-groups representing different cultures in Latvia serves as a base for interpretation of current situation where communication challenges can occur as a result of interaction between people with different cultural backgrounds. The article approves the idea to elaborate the new specific model for multicultural communication, and after analysis highlights the base and components of this new model.